Efficacy of a vaccine based on protective antigen and killed spores against experimental inhalational anthrax - Gauthier, Yves P; Tournier, Jean-Nicolas; Paucod, Jean-Charles; Corre, Jean-Philippe; Mock, Michèle; Goossens, Pierre L; Vidal, Dominique R (Infection and immunity, 2009)
Protective antigen (PA)-based anthrax vaccines acting on toxins are less effective than live attenuated vaccines, suggesting that additional antigens may contribute to protective immunity. Several reports indicate that capsule or spore-associated antigens may enhance the protection afforded by PA. Addition of formaldehyde-inactivated spores (FIS) to PA (PA-FIS) elicits total protection against cutaneous anthrax. Nevertheless, vaccines that are effective against cutaneous anthrax may not be so against inhalational anthrax. The aim of this work was to optimize immunization with PA-FIS and to assess vaccine efficacy against inhalational anthrax. We assessed the immune response to recombinant anthrax PA from Bacillus anthracis (rPA)-FIS administered by various immunization protocols and the protection provided to mice and guinea pigs infected through the respiratory route with spores of a virulent strain of B. anthracis. Combined subcutaneous plus intranasal immunization of mice yielded a mucosal immunoglobulin G response to rPA that was more than 20 times higher than that in lung mucosal secretions after subcutaneous vaccination. The titers of toxin-neutralizing antibody and antispore antibody were also significantly higher: nine and eight times higher, respectively. The optimized immunization elicited total protection of mice intranasally infected with the virulent B. anthracis strain 17JB. Guinea pigs were fully protected, both against an intranasal challenge with 100 50% lethal doses (LD(50)) and against an aerosol with 75 LD(50) of spores of the highly virulent strain 9602. Conversely, immunization with PA alone did not elicit protection. These results demonstrate that the association of PA and spores is very much more effective than PA alone against experimental inhalational anthrax.